2001
DOI: 10.1021/jf010086v
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Scavenging Activities Measured by Electron Spin Resonance Spectroscopy and B16 Cell Antiproliferative Behaviors of Seven Plants

Abstract: In an effort to discover new antioxidant natural compounds, seven plants that grow in France (most of them in the Limousin countryside) were screened. Among these plants, was the extensively studied Vitis vinifera as reference. For each plant, sequential percolation was realized with five solvents of increasing polarities (hexane, chloroform, ethyl acetate, methanol, and water). Free radical scavenging activities were examined in different systems using electron spin resonance (ESR) spectroscopy. These assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
88
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 28 publications
(37 reference statements)
6
88
1
Order By: Relevance
“…The available studies in literature described phenolic composition in C. sativa leaves (Calliste et al, 2001) and heartwood (Sanz et al, 2010), but not in its flowers. The phenolic composition of F. ulmaria flowers was studied, but with plant material from other European countries, i.e not growing under Mediterranean particular climatic and soil conditions Shilova et al, 2006;Pemp et al, 2007;Fecka, 2009;Harbourne et al, 2009;Krasnov et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The available studies in literature described phenolic composition in C. sativa leaves (Calliste et al, 2001) and heartwood (Sanz et al, 2010), but not in its flowers. The phenolic composition of F. ulmaria flowers was studied, but with plant material from other European countries, i.e not growing under Mediterranean particular climatic and soil conditions Shilova et al, 2006;Pemp et al, 2007;Fecka, 2009;Harbourne et al, 2009;Krasnov et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of natural antioxidantsare phenolic compounds or polyphenols and the antioxidant activity of many natural extracts and essential oils is due to such phenolic compounds. The antioxidant activity of phenolic compounds is mainly due to their redox properties, simultaneous hydrogen atom donation to free radicals, electron transfer and metal chelating [26]. Lee et al (2005) showed that the main components dichloromethane extract of T. vulgaris, particularly eugenol, thymol and carvacrol, have higher antioxidant activity than synthetic antioxidant BHT and α-tocopherol [27].Other compounds isolated from thyme that showed strong antioxidant activity are caffeic and rosmarinic acid, biphenyl compounds of monoterpenoid origin, flavanones (narirutin, eriodictyol, eriocitrin, hesperidin), methyl rosmarinate [28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…Herbals and herbal extracts, which contain different classes of polyphenols, are very attractive, not only in modern phytotherapy, but also for the food industry, due to their use as preservatives. It has been reported (Calliste, Trouillas, Allais, Simon,& Duroux, 2001) that phenolic acids and their glycosides,aglycones, and monoglycosyl or diglycosyl flavonoids are distributed in the different solvents as a function of polarity and water extracts contain the most polar compounds. These facts might explain the strong scavenging and antioxidant activity of water extracts of Phoenix dactylifera, Citrus aurantifolia.…”
Section: Resultsmentioning
confidence: 99%